Economic and regulatory analysis of natural gas in Brazil: electricity generation, infrastructure, and energy integration. - Leal, Fernando Inti (2018)
Brazil\'s discoveries of large gas reservoirs in the offshore ultra-deep waters of the presalt fields show a promising scenario, along with strategic investment and adequate policy, for the development of natural gas infrastructure and a sustainable transition in the Brazilian electricity mix. Such transition should occur through the use of transnational natural gas pipelines connected to large industrial facilities and power stations, as part of strategic planning to expand industrial usage, and avoid the shortage of electricity supply, with economic and environmental advantages. Since the most important debates of the new millennium are focused on globalization and sustainable development for nations, transnational energy integration in Latin America has been receiving increasingly attention from researchers and policy makers. In this overall context, the purpose of the present research was to develop a model to study, in a comparative manner, the thermoelectric generation, as well as to analyze the effect of legal frameworks and governmental policies on the development of infrastructure and natural gas market in Brazil, with a detailed study of the most relevant market and regulatory mechanisms. A comparison was performed in terms of the most relevant regulatory legislation in Brazil and other relevant Member States of the South American economic block. The study also evaluates the sanctions imposed by ANEEL Resolution n. 583 of 2013 on suppliers, due to the lack of NG supply for thermoelectric utilities, proposing an alternative formula, thought to mitigate the influence of averages and other electricity market parameters, therefore decreasing the sanction value for the NG supplier, without compromising the contract neutrality. Different factors were analyzed in order to determine which technology would be the most efficient in terms of levelized costs. Results indicated that natural gas-fired generators are very competitive and efficient, when compared to other thermoelectric sources in both economic and environmental aspects, even when externalities were included. Also, that further strategic investment and adequate regulatory policy changes are required from the market agents, in order to foster the development of pipeline infrastructure and the expansion of natural gas use in Brazil. The study also demonstrates that the environmental impact of the CH4 leakage equals that of CO2 release from combustion at about 4.2% leakage on a mass basis, when methane leakage rises to a level in which natural gas becomes as greenhouse gas intensive as biomass.